PRA-RANCANGAN PABRIK AMMONIUM NITRAT DENGAN PROSES UHDE KAPASITAS 340.000 TONTAHUN: PRA-RANCANGAN PABRIK AMMONIUM NITRAT DENGAN PROSES UHDE KAPASITAS 340.000 TONTAHUN - Ebersa Desry (Journal Of Social Research, 2022)
Ammonium Nitrate with the chemical formula NH4NO3 is a white solid inthe form of a crystal that easily absorbs water (hygroscopic). Most of AmmoniumNitrate products are used as explosives for coal mining, mineral mining, andmilitary explosives, and a small portion is used as a mixture of fertilizers andpharmacy. Ammonium nirate is needed both domestically and abroad.The UHDE process reacted Ammonia and Nitric Acid gas in a bubblingreactor with neutralization reaction at a temperature of 170-180ºC and a pressureof 4-5 bar. the reactor output is pumped to the evaporator to be concentrated. Thesolution comes out of the evaporator by entering the prilling tower, the prillAmmonium Nitrate formed is dried, screened, cooled and coated with a coatingagent to obtain the desired prill Ammonium Nitrate.The plant was built in the Kaltim Industrial Estate area to facilitatetransportation of raw materials and products. As well as being close to the watertreatment industry so as to facilitate the fulfillment of factory water consisting ofwater sanitation, cooling water, boiler feed water. Electricity requirements forplant operations are met from PT. PLN persero and backup generator.The form of the ammonium nitrate plant is an Perseroan Terbatas (PT) with191 employees with a line, functional and staff organization system. The plantoperates 24 hours / day for 330 days / year.From economic analysis obtained percent profit on sales after tax is19.26%. percent return on investment after tax is 64.92%. Pay-out time based onthe cumulative cash flow is 4 years. The rate of return is obtained at 34.97%. Thisvalue is higher than the bank loan interest rates in Indonesia, which are 8-11%.Break even point at production capacity of 16.29% shutdown point at productioncapacity of 10.49%. Based on the above economic analysis, an ammonium nitrateplant with a capacity of 340,000 tons / year is feasible to be established.Keyword : ammonium nitrate,ammonia, nitric acid, UHDE, Bubble Reactor.